Transient risk factors of acute occupational injuries: a case-crossover study in two Danish emergency departments - Anna H Østerlund; Flemming Lander; Karina Nielsen; Pete Kines; Jette Möller; Jens Lauritsen (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: The objectives of this study were to (i) identify transient risk factors of occupational injuries and (ii) determine if the risk varies with age, injury severity, job task, and industry risk level. METHOD: A case-crossover design was used to examine the effect of seven specific transient risk factors (time pressure, disagreement with someone, feeling sick, being distracted by someone, non-routine task, altered surroundings, and broken machinery and materials) for occupational injuries. In the study, 1693 patients with occupational injuries were recruited from a total of 4002 occupational injuries seen in 2013 at two emergency departments in Denmark. Effect estimates were calculated using the matched-pair interval approach. RESULTS: Increased risk for an occupational injury was found for time pressure [odds ratio (OR) 1.6, 95% confidence interval (95% CI) 1.3-2.0], feeling sick (OR 2.7, 95% CI 1.9-3.9), being distracted by someone (OR 3.1, 95% CI 2.3-4.1), non-routine task (OR 8.2, 95% CI 5.3-12.5), altered surroundings (OR 20.9, 95% CI 12.2-35.8), and broken machinery or materials (OR 20.6, 95% CI 13.5-31.7). The risk of occupational injury did not vary substantially in relation to sex, age, job task, industry risk level, or injury severity. CONCLUSION: Use of a case-crossover design identified several worker-related transient risk factors (time pressure, feeling sick, being distracted by someone) that led to significantly increased risks for occupational injuries. In particular, equipment (broken machinery or materials) and work-practice-related factors (non-routine task and altered surroundings) increased the risk of an occupational injury. Elaboration of results in relation to hazard period and information bias is warranted.